Preparation of biochar materials and their research progress in supercapacitors - Wang, Mengqian; Zhang, Yalin; Li, Tianwang; Jin, Yinyin; Cai, Yanqing (International Journal of Materials Science and Technology Studies, 2024)
With the depletion of fossil fuels causing a series of energy and environmental problems, accelerating the development of green and clean energy is urgent. Supercapacitors are favored by researchers due to their excellent performance such as high specific energy and good stability. Biochar is obtained from biomass materials after pre-carbonization and activation treatment, with developed pore size, high active specific surface area, and abundant resources. It has good application prospects as a supercapacitor material. This article provides a brief introduction to biomass charcoal materials and introduces the preparation methods of biomass charcoal and its research progress in the field of supercapacitors. Finally, it looks forward to the development trend of biomass charcoal materials, providing a reference for further improving the research application of biomass charcoal materials in the field of supercapacitors in the future.